DAYA TARIK WISATA AIR TERJUN GUNUNG SERINDUNG DI KECAMATAN SALATIGA KABUPATEN SAMBAS - arto, Joni; Nugroho R, Joko; Widiastuti, Tri (Universitas Tanjungpura, 2013)
Waterfall Regionis located in Mount Serindung hilly or mountainous area in Salatiga District which is one of the Protected Forest areas.Waterfall Region Mount Serindung has potential tourist development prospects with the potential floras and faunas are interesting and have some attraction in the form of waterfalls, natural beauty, floras and faunas of the forest and surrounding scenery are Serindung Mountain Falls. This research aims to obtain data on the potential appeal contained in theWaterfall region of Mount Serindung to develop tourism in the region. The benefit of this research is to provide better information on potential natural diversity of floras and faunas as well as the natural beauty that can be used as a tourist attraction in the Waterfall region of Mount Serindung.The research was conducted in the Waterfall region of Mount Serindung on August 26,2012 until September 30,2012,by using descriptive method that describes all potential objects of research that has been observed and analyzed by using a standard observation Raw Size Guidelines / Standards Assessment and Development of Attraction nature. Assessment parameters consist of natural beauty, unique natural resources, natural resources stand, the integrity of natural resources, natural resource sensitivity, choice of leisure activities, clean air and space visitors. Based on calculations of the entire acreage acquired attractiveness criteria 948.12 value. When compared with classification based Development Element Weighted Value Waterfall Mountain Serindung it has the potential appeal of a good area (B). This value indicates that Nature Waterfall Mountain Serindung can be used asa tourist destination. Key word : Serindung Mountain,Waterfall, Tourist Attraction